269 Evolution of the Child Drowning Prevention Programme in Thailand. (1st September 2016) - Gerdmongkolgan, Suchada; Ekchaloemkiet, Som
Abstract : Background: Drowning is the number one cause of death among children under 15 years of age in Thailand, taking into account all deaths due to infectious and non-infectious diseases. Child drowning death rate (per 100, 000 child population) ranged from 6.8 to 11.5 between 2004 and 2014. The Child Drowning Prevention Programme in Thailand has been implemented since late 2006 with the goal of reducing the child drowning death rate to 5.0 by 2018. The Objective of this study is to develop the standards for the operations of the Child Drowning Prevention Programme in Thailand. Methods: The operations of the Child Drowning Prevention Programme in Thailand during the period 2006–2014 were reviewed and then a gap analysis was conducted for use as a guide for developing the standards, or bridging the gap, for the operations of the programme. Results: After implementing several of such measures, the child drowning death rate declined constantly from 11.5 in 2005 (the first year of programme implementation) to 6.8 in 2014. But gaps were noted at the local or community level, such as the lack of continuity, encouragement and operations of in all aspects of the programme. Thus, to bridge the gaps, in 2015 the Ministry of Public Health adopts the "Merit Maker for Child Drowning Prevention" measure, aiming to identify the networks working on drowning prevention that covers at least six key measures, emphasising community-based multi-disciplinary approach, resource sharing, participation of local agencies, and rewarding Merit Makers whose contributions are in accordance with the established criteria. Conclusion: Since the launch of the programme on child drowning prevention, policies and measures have been implemented, resulting in a constant reduction in child drowning fatalities. In such efforts, the Ministry of Public Health has also revised several measures so that they are more effective in the country in achieving the child drowning reduction goal.